2019
DOI: 10.1515/pac-2019-1004
|View full text |Cite
|
Sign up to set email alerts
|

A surprising mechanism lacking the Ni(0) state during the Ni(II)-catalyzed P–C cross-coupling reaction performed in the absence of a reducing agent – An experimental and a theoretical study

Abstract: The Hirao reaction, i.e. the P–C coupling between a bromoarene and a >P(O)H reagent performed in most cases in the presence of a Pd(0) complex incorporating a P-ligand may also be carried out applying a Ni(II) catalyst precursor with or without Zn or Mg as the reducing agent. The Ni catalysts may include P- or N-ligands. B3LYP/6-31G(d,p)//PCM(MeCN) quantum chemical calculations suggested that the mechanism of the NiX2 catalyzed (X=Cl or Br) P–C couplings performed in the absence of a reducing agent, and in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 47 publications
2
15
0
Order By: Relevance
“…We decided to return to the Ni(II) → Ni(IV) → Ni(II) protocol, which was proved to be a realistic route applying P -ligands. 32 The catalytic process starting with Ni(II)-bipyridyl complex II was also evaluated by the M06-2 X /6-31G(d,p)//PCM(MeCN) method. The II → VII → VI → VIII → 11 → 12 → 13 → ( 14 + 3a ) route proposed is summarized in Figure 5 , while the energetics are listed in Table 7 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We decided to return to the Ni(II) → Ni(IV) → Ni(II) protocol, which was proved to be a realistic route applying P -ligands. 32 The catalytic process starting with Ni(II)-bipyridyl complex II was also evaluated by the M06-2 X /6-31G(d,p)//PCM(MeCN) method. The II → VII → VI → VIII → 11 → 12 → 13 → ( 14 + 3a ) route proposed is summarized in Figure 5 , while the energetics are listed in Table 7 .…”
Section: Resultsmentioning
confidence: 99%
“…The MW-assisted reactions were performed according to our earlier methods. 31 , 32 To a MW glass vessel was added 0.0065 g (0.050 mmol) of nickel chloride, 0.052 mL (0.50 mmol) of bromobenzene, 0.12 g (0.60 mmol) of diphenylphosphine oxide ( 2a ) or 0.090 mL (0.60 mmol) of ethyl phenyl- H -phosphinate ( 2b ), 0.16 g (0.50 mmol) of cesium carbonate, and 1 mL of acetonitrile. In one case ( Table 2 , entry 15), 0.039 g of (0.6 mmol) zinc powder was also added.…”
Section: Methodsmentioning
confidence: 99%
“…It follows that, as a result, Ni(II) gets in the Ni(IV) state. This was indeed a fully surprising experience, but quantum chemical calculations confirmed this [ 71 ]. It was another surprise that in the “reductive” variation, again a Ni(II) → Ni(IV) oxidation was substantiated by the preparative experiments and calculations [ 72 ].…”
Section: Catalysts For the Ni-assisted Hirao Reactionsmentioning
confidence: 89%
“…In our case, the excess of the >P(O)H reagent served as the P-ligand. Preparative experiments suggested that two equivalents of the P-reagent to the NiCl 2 was the optimum quantity [ 47 , 71 ]. Then, theoretical calculations suggested the following mechanism for the formation of the active catalyst entering in the Hirao reaction ( Scheme 11 ) [ 71 ].…”
Section: Catalysts For the Ni-assisted Hirao Reactionsmentioning
confidence: 99%
See 1 more Smart Citation